A Mathematical Approach Using Strat-M® to Predict the Percutaneous Absorption of Chemicals under Finite Dose Conditions - Ryoki Kunita; Takafumi Nishijima; Hiroaki Todo; Kenji Sugibayashi; Hitoshi Sakaguchi (MDPI AG, 2022)
Estimation of the percutaneous absorption is essential for the safety assessment of cosmetic and dermopharmaceutical products. Currently, an artificial membrane, Strat-M®, has been focused on as the tool which could obtain the permeation parameters close to the skin-derived values. Nevertheless, few practical methodologies using the permeation parameters for assessing percutaneous absorption under in-use conditions are available. In the present study, based on Fick's first law of diffusion, a novel mathematical model incorporating the permeation parameters as well as considering the water evaporation (Teva) was constructed. Then, to evaluate the applicability domain of our model in the case where Strat-M®-derived parameters were used, the permeation parameters were compared between the skin from edible porcine and Strat-M®. Regarding chemicals (−0.2 ≤ Log Kow ≤ 2.0), their permeation profiles were equivalent between Strat-M® and porcine skin. Therefore, for these chemicals, the percutaneous absorption was calculated using our model with the permeation parameters obtained using Strat-M® and the Teva determined by measuring the solution weight. The calculated values revealed a good correlation to the values obtained using porcine skin in finite dose experiments, suggesting that our mathematical approach with Strat-M® would be useful for the future safety assessment of cosmetic and dermopharmaceutical products.